Effect of Cytokine Signaling 3 Gene Polymorphisms in Childhood Obesity - (:unkn) unknown (My University, 2016)
0

Objective: Although polymorphisms in suppressor of cytokine signaling 3 (SOCS3) was reported to be related to obesity, Metabolic syndrome (MS), and type 2 diabetes mellitus in various adult studies, there is a lack of data in children. In this study, we examined eight reported polymorphisms of SOCS3 in obese Turkish children and adolescent with and without MS and compared the results with that of controls. Methods: One hundred and forty eight obese and 63 age- and sex-matched control subjects were enrolled in the study. Obesity classification was carried out according to body mass index. World Health Organization and National Cholesterol Education Program criteria were used for the diagnosis of MS. Genotyping procedure was carried out by polymerase chain reaction and Sanger sequencing protocol. Results: The frequency of rs2280148 polymorphism was significantly higher in obese subjects with MS than in the control group, whereas the frequency of rs8064821 polymorphism was significantly higher in obese subjects with MS than in obese children without MS. Conclusion: The significant associations of certain SOCS3 polymorphisms with obesity parameters in both MS and MS -related insulin resistance, hypertension, and fatty liver suggest that polymorphisms in this gene may play a role in the pathogenesis of MS and also that they can be potentially used as a marker for attenuated or aggressive disease.
Keywords: Endokrinoloji ve Metabolizma; Pediatri